Potentials of lignocellulosic agricultural residues in paper production - Plazonić, Ivana (Array, 2021)
Surface characteristics of printing substrates are of the utmost importance to all types of paper that interact with ink. During all types of printing processes, the behaviour of the liquid phase (ink or dye) on the paper is directly defined by the paper cellulose-based surface. The printed ink spreads and penetrates more into paper fibres when the paper surface is rougher and more permeable. Contact angle measurements by sessile drop method are considered the most appropriate for determining the paper sheet surface energy. Paper as hydrophilic material has a high absorption rate resulting in a low contact angle. The objective of this study was to evaluate the surface free energy of laboratory-made papers containing straw pulp obtained from residues after the harvest of the most cultivated cereals in Croatia (wheat, barley and triticale). The obtained surface free energy results are promising for straw pulp usage in the manufacture of printing paper.